(untitled) (Annals of Medical Research, 2023)
Aim: Analysing the efficancy of The Dutch COVID-19 Reporting and Data System (CO-RADS) classification to evaluate the severity of the disease of patients with COVID-19 infection and investigating its diagnostic performance with the correlation between reverse transcriptase-polymerase chain reaction (RT-PCR) test results and severity of the disease. Materials and Methods: Retrospective evaluation of the RT-PCR and the Computed Tomography (CT) imaging results of 519 patients who were clinically accepted and threated as Covid-19. Inclusion criteria: All patients over the age of 18 who underwent CT with a pre-diagnosis of covid were included. The study excluded patients who were under the age of 18, pregnant, in poor general health but unable to undergo a CT scan, whose data could not be retrieved, or whose data were input insufficiently. Three radiologists evaluated the Chest CT images by using the CO-RADS and the CT Score classifications. Relationship between CORADS, Chest CT Score and RT-PCR results were demonstrated. Demographic data, clinical features, comorbidities, hospitalization rates and intensive care unit admission were recorded and correlated with CORADS and CT Score classification. Results: The average age was 46.41± 17.37 (range 18-95). 232 cases were women, while 287 cases were men. 278 (53.5 %) of 519 patients had positive RT-PCR results. According to kappa results; there is no agreement between CORADS and RT-PCR, CORADS and CT Score. 278 (53,6 %) of 519 patients had positive RT-PCR results. According to kappa results; there is no agreement between CO-RADS and RT-PCR, CORADS and CT Score. There was correlation between CT score and man population (p <0,037). According to the clinical symptoms; only sore throat was correlated with CORADS while fever, cough and dsypnea were not. Hospitalization and ICU admission were higher in CORADS 2-5 group. 84 of 165 patients with CORADS 1 had RT PCR positive results; while160 of 354 patients with lung involvement (CORADS 2-5 group) on CT images were RT-PCR negative. Conclusion: Using CO-RADS classification with RT-PCR improves more accurate diagnosis. Using CT Score and CORADS classification with clinical features, enpowers the triage options during the peak of pandemic wave.